Simultaneous Ribosome Profiling of Human Host Cells Infected with Toxoplasma gondii - Michael J. Holmes (American Society for Microbiology, 2019)
ABSTRACT Toxoplasma gondii is a ubiquitous obligate intracellular parasite that infects the nucleated cells of warm-blooded animals. From within the parasitophorous vacuole in which they reside, Toxoplasma tachyzoites secrete an arsenal of effector proteins that can reprogram host gene expression to facilitate parasite survival and replication. Gaining a better understanding of how host gene expression is altered upon infection is central for understanding parasite strategies for host invasion and for developing new parasite therapies. Here, we applied ribosome profiling coupled with mRNA measurements to concurrently study gene expression in the parasite and in host human foreskin fibroblasts. By examining the parasite transcriptome and translatome, we identified potential upstream open reading frames that may permit the stress-induced preferential translation of parasite mRNAs. We also determined that tachyzoites reduce host death-associated pathways and increase survival, proliferation, and motility in both quiescent and proliferative host cell models of infection. Additionally, proliferative cells alter their gene expression in ways that are consistent with massive transcriptional rewiring, while quiescent cells were best characterized by reentry into the cell cycle. We also identified a translational control regimen consistent with mechanistic target of rapamycin (mTOR) activation in quiescent cells and, to a lesser degree, in proliferative cells. This study illustrates the utility of the method for dissection of gene expression programs simultaneously in the parasite and host. IMPORTANCE Toxoplasma gondii is a single-celled parasite that has infected up to one-third of the world’s population. Significant overhauls in gene expression in both the parasite and the host cell accompany parasite invasion, and a better understanding of these changes may lead to the development of new therapeutic agents. In this study, we employed ribosome profiling to determine the changes that occur at the levels of transcription and translation in both the parasite and the infected host cell at the same time. We discovered features of Toxoplasma mRNAs that suggest a means for controlling parasite gene expression under stressful conditions. We also show that differences in host gene expression occur depending on whether they are confluent or not. Our findings demonstrate the feasibility of using ribosomal profiling to interrogate the host-parasite dynamic under a variety of conditions.